2017
DOI: 10.1186/s12906-017-1898-6
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol on comparative effectiveness of mindfulness meditation and qigong on psychophysiological outcomes for patients with colorectal cancer: a randomized controlled trial

Abstract: BackgroundColorectal cancer imposes threats to patients’ well-being. Although most physical symptoms can be managed by medication, psychosocial stressors may complicate survival and hamper quality of life. Mindfulness and Qigong, two kinds of mind-body exercise rooted in Eastern health philosophy, has been found effective in symptoms management, improving mental health, and reducing stress. With these potential benefits, a randomized controlled trial (RCT) is planned to investigate the comparative effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Previous studies have suggested that mind-body exercise (movement-based mind-body intervention) that combines physical exercise postures with breathing and deep relaxation (Wells et al, 2019) can significantly improve cognitive function in individuals with MCI (Shuo et al, 2018; Sungkarat et al, 2017, Sungkarat et al, 2018). As a popular mind-body exercise, Baduanjin is unique and much simpler to learn than other mind-body exercises such as Tai Chi (Liao et al, 2015), making it an optimal choice for older individuals with cognitive decline (Ho et al, 2017). Previous studies have suggested that compared to jogging, Baduanjin can prevent normal age-related memory decline, delaying the effects of aging (Fiatarone et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that mind-body exercise (movement-based mind-body intervention) that combines physical exercise postures with breathing and deep relaxation (Wells et al, 2019) can significantly improve cognitive function in individuals with MCI (Shuo et al, 2018; Sungkarat et al, 2017, Sungkarat et al, 2018). As a popular mind-body exercise, Baduanjin is unique and much simpler to learn than other mind-body exercises such as Tai Chi (Liao et al, 2015), making it an optimal choice for older individuals with cognitive decline (Ho et al, 2017). Previous studies have suggested that compared to jogging, Baduanjin can prevent normal age-related memory decline, delaying the effects of aging (Fiatarone et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of traditional Chinese medicine qigong, Baduanjin usually involves exercises that integrate the body and mind, which can balance the body's yin and yang, promote blood circulation, and maximize physical and mental health [23]. More and more studies have found that combining with Baduanjin exercise can signi cantly improve the prognosis of clinical chronic diseases [24].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies cited elsewhere in this paper have found that the use of qigong or tai chi has reduced depression in cancer patients. Henshall, et al [94] found that to be the case for lung cancer patients. Gaik [95] wrote a doctoral thesis examining the effect of Spring Forest Qigong [96] on depression.…”
Section: Depression and Cancermentioning
confidence: 98%
“…Henshall, Allin and Aveyard [94] examined numerous prior studies and found that an exercise regimen often had a significant effect on reducing dyspnea (shortness of breath).…”
Section: Dyspnea and Cancermentioning
confidence: 99%